Primary lacrimal gland sebaceous carcinoma–case presentation and literature review - Schellini, Silvana A. [UNESP]; Santos Souza, Daniela [UNESP]; Almeida, Amanda A. M. P. [UNESP]; Schellini, Rodolfo A. [UNESP]; Ferraz, Lucieni C. B. (Taylor & Francis, 2023)
Primary sebaceous carcinoma of the lacrimal gland (PSCLG) is the rarest lacrimal gland (LG) tumor, often belatedly diagnosed, worsening the prognosis. We present a 68-year-old man with a large, indurated mass in the left orbital outer quadrant, visible at the conjunctival upper temporal fornix, extending to the lower fornix, with left gaze restriction. The lesion was not related to the eyelid or other periocular tissues. Excisional biopsy revealed the PSCLG diagnosis. There are only eight others previous PSCLGs. Males are the most affected. Indurated mass in the lacrimal fossa, with eyelid in “S” shape is the most common presentation. Image exams are suggestive, but histological and immunohistochemical evaluations showing a single tumor cell line within LG are mandatory for definitive diagnosis. Larger and more extensive lesions can have a poor prognosis, but early detection can favor the outcome.
Keywords: case report; lacrimal gland; literature revision; Primary sebaceous carcinoma